2012
DOI: 10.1016/j.bbamem.2011.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-associated protein (CD47) is a putative mediator for soluble fibrinogen interaction with human red blood cells membrane

Abstract: Fibrinogen is a multifunctional plasma protein that plays a crucial role in several biological processes. Elevated fibrinogen induces erythrocyte hyperaggregation, suggesting an interaction between this protein and red blood cells (RBCs). Several studies support the concept that fibrinogen interacts with RBC membrane and this binding, due to specific and non-specific mechanisms, may be a trigger to RBC hyperaggregation in inflammation. The main goals of our work were to prove that human RBCs are able to specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 47 publications
0
59
1
Order By: Relevance
“…Although previous studies demonstrated specific interactions between fibrin and RBCs, [28][29][30] and implicate CD47 45 and a b3-like molecule 46 on the RBC surface, we were unable to detect any FXIIIa substrates on the RBC surface. We were also unable to detect differences in retention of young vs old RBCs in clots (data not shown), indicating age-dependent changes in RBC protein expression or morphology 47 do not influence their presence in clots.…”
Section: Discussioncontrasting
confidence: 44%
“…Although previous studies demonstrated specific interactions between fibrin and RBCs, [28][29][30] and implicate CD47 45 and a b3-like molecule 46 on the RBC surface, we were unable to detect any FXIIIa substrates on the RBC surface. We were also unable to detect differences in retention of young vs old RBCs in clots (data not shown), indicating age-dependent changes in RBC protein expression or morphology 47 do not influence their presence in clots.…”
Section: Discussioncontrasting
confidence: 44%
“…It is important to highlight that recently we described that CD47 is a putative binding site for fibrinogen at erythrocyte membrane (de Oliveira et al, 2012). Erythrocyte membrane CD47 at the complex Table 1 Mean values of erythrocyte elongation index (EEI) expressed in percentage obtained at shear stress values varied from 0.3 and 60.0 Pa.…”
Section: Discussionmentioning
confidence: 99%
“…So, cAMP synthesis, are affected by the presence of AChE-timolol less active form and by Fib-CD47 receptor complex because both type of complexes are associated to Gi protein and consequently adenylyl cyclase inhibition [4,9,10]. Our results evidenced the effect of Fib in ED is synergic with timolol plus or not with MDL because maintaining cAMP synthesis inhibited.…”
Section: Discussionmentioning
confidence: 49%
“…Fibrinogen binding to erythrocyte CD47 receptor protein belonging to Rh complex that stablish contact with 4.2 cytoskeletal protein which interact with band 3 protein [4,15]. Mimicking, in vitro hyperfibrinogenemia increased values of nitric oxide (NO) efflux from RBCs dependent on band 3 protein phosphorylation degree and lower cyclic adenosine monophosphate (cAMP) concentration was evidenced [6,7].…”
Section: Introductionmentioning
confidence: 99%